2011
DOI: 10.1002/cncr.26594
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time detection of hepatic micrometastases from pancreatic cancer by intraoperative fluorescence imaging

Abstract: BACKGROUND: Recently, a highly sensitive fluorescent imaging technique was developed for the real-time identification of hepatic tumors. The authors applied this procedure for the intraoperative detection of radiographically occult hepatic micrometastases from pancreatic cancer. METHODS: Forty-nine consecutive patients with pancreatic cancer who underwent surgical intervention were examined. Preoperative clinical images had not revealed any hepatic metastases. On the day before surgery, indocyanine green was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 43 publications
3
70
0
Order By: Relevance
“…At the same time, Gotoh et al reported the results of ICG fluorescence imaging of 14 HCCs (10 cases) that included 4 nodules first discovered by this technique [2]. Yokoyama et al recently added a report on the possibility of applying ICG fluorescence imaging to the intraoperative diagnosis of micrometastases of pancreatic cancer [20].…”
Section: Discovery Of Fluorescence Imaging Of Liver Cancermentioning
confidence: 99%
“…At the same time, Gotoh et al reported the results of ICG fluorescence imaging of 14 HCCs (10 cases) that included 4 nodules first discovered by this technique [2]. Yokoyama et al recently added a report on the possibility of applying ICG fluorescence imaging to the intraoperative diagnosis of micrometastases of pancreatic cancer [20].…”
Section: Discovery Of Fluorescence Imaging Of Liver Cancermentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A total of 718 cases were globally analyzed as study group. No side effects of ICG were reported in any articles.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenously administered ICG has also been used in NIR endoscopy systems to successfully differentiate superficial gastric tumors from invasive cancers (13). ICG has been shown to localize to both hepatocellular carcinoma and intrahepatic metastases 24-72 hours after injection with high target-to-background ratios (2,3,6). The mechanism by which ICG localizes to intrahepatic metastases has recently begun to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Ill (2)(3)(4)(5)(6). The intraoperative imaging of ICG for the detection of intrahepatic malignancy has been demonstrated (2,3,6).…”
Section: Molecular Imaging: Interventional Optical Molecular Imaging mentioning
confidence: 99%
See 1 more Smart Citation